Autism – risk factors and treatment - Wójcik, Magdalena; Boreński, Grzegorz; Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Autism spectrum disorder (ASD) is a group of pervasive neurodevelopmental disorders that are characterized by persistent moderate to severe impairment in social skills and communication but also repetitive or stereotyped behaviours and interests. Many factors have been suggested to cause autism. However, its aetiology is still not fully understood. There are many kinds of treatments: behavioural treatment, pharmacological approach and alternative medicine (CAM) therapies.The aim of the study: The purpose of this systemic review was to collect and analyse available data about aetiology and treatment of ASD.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: autism spectrum disorder, aetiology, treatment.Description of the state of knowledge: The study that is one of the biggest population-based twin studies of autism shows that heritability of autism is around 55%. Literature reports that approximately 10% children with autism or ASD have other chromosomal or genetic disorder and the most common is Fragile X and it is the most common cause of autism. Several environmental risk factors were thought to be the cause of autism. Nevertheless, only some of them might have an influence on developing ASD. There are many forms of behavioural treatment, but only two drugs were approved for ASD symptoms treatment. CAM offers many different therapies but their efficiency is not strong enough. Summary: The aetiology of ASD remains unclear. Reports of different factors being cause of developing ASD are not consistent. When it comes to treatment, early diagnosis and intervention are very important and can result in better onset of the disorder. ASD is subject of many researches but still even more is needed to answer the questions of aetiology and successful treatment of ASD.